1994
DOI: 10.1002/eji.1830240412
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ mobilization in physiologically stimulated single T cells gradually increases with peptide concentration (analog signaling)

Abstract: We have investigated Ca2+ mobilization in single T cells stimulated with their physiological ligand, i.e. antigenic peptide bound to major histocompatibility complex (MHC) molecules on antigen-presenting cells (APC). Fibroblasts expressing I-Ed class II molecules were pulsed with a peptide derived from the lambda 2(315) immunoglobulin light chain. Onto such antigen-pulsed fibroblasts were sedimented cloned Th1 cells loaded with Fura-2. Changes in cytosolic Ca2+ concentration in single T cells were continually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Ca 2ϩ mobilization measurements were performed as previously described (14). Briefly, rested T18 CD4 ϩ T cells were incubated with 5 M fura2-axetoxymethyl ester (fura2-AM; Teflabs, Austin TX) and resuspended in HEPES salt solution (10 mM HEPES and 11 mM D-glucose).…”
Section: Measurements Of Free Cytosolic Ca 2ϩ In Single T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2ϩ mobilization measurements were performed as previously described (14). Briefly, rested T18 CD4 ϩ T cells were incubated with 5 M fura2-axetoxymethyl ester (fura2-AM; Teflabs, Austin TX) and resuspended in HEPES salt solution (10 mM HEPES and 11 mM D-glucose).…”
Section: Measurements Of Free Cytosolic Ca 2ϩ In Single T Cellsmentioning
confidence: 99%
“…The cells were incubated for 2 or 4 h at 37°C before washing and fura2-AM-loaded T cells (5 ϫ 10 5 /w) were carefully added and allowed to sediment onto the layer of mAb-pulsed monocytes. The imaging and registration software were as described elsewhere (14). Statistical analyses were computed by using SPSS for Windows (Chicago, IL).…”
Section: Measurements Of Free Cytosolic Ca 2ϩ In Single T Cellsmentioning
confidence: 99%
“…Ca 2+ mobilization measurements were performed as previously described [28]. Briefly, rested T18 CD4 + T cells were incubated with 5 ?…”
Section: Measurements Of Free Cytosolic Ca 2+ In Single T Cells To Inmentioning
confidence: 99%
“…To be able to compare the Ca 2+ responses, traces were synchronized so that time point 30 s indicate the initial rise in cytosolic Ca 2+ upon T cell contact with monocytes. The imaging and registration software were as described [28]. Statistical analyses were computed by using SPSS for Windows (Chicago, IL).…”
Section: Measurements Of Free Cytosolic Ca 2+ In Single T Cells To Inmentioning
confidence: 99%
“…[11][12][13][14]31 During the preparation of this manuscript we became aware of the data recently published by Alvarez and Russell, 32 who used a model system using Jurkat T cells with tetracycline-regulatable ch-Rec densities to study their level of IL-2 response as a function of plastic-coated antigen density. They concluded that Jurkat T cells can be engineered to discriminate…”
Section: Figure 4 Ch-rec High-pos Ctls Can Lyse Taa Low-pos Tumor Celmentioning
confidence: 99%